Study of catalytic cracking process of fuel oil to obtain components of motor fuels using aerosol nanocatalysis technology - SV Leonenko; SA Kudryavtsev; IM Glikina (Adsorption Science & Technology, 2017)
The article presents the results of the investigation of catalytic cracking process of crude oil in a distillation column, under atmospheric pressure, the active component of the catalyst being type Y zeolite. The process was carried out under the conditions of a new technology, called “aerosol nanocatalysis.” A schematic diagram of the laboratory installation is described and comparison of the experimental data with thermal cracking processes is made, and the expected technical and economic indicators of the new and existing industrial technologies are compared. It is shown that the use of zeolite-containing catalyst (type Y) leads to increased yield of light oil products by 48–85% by weight compared to thermal cracking. The technology of aerosol nanocatalysis is promising as it is energy and resource-saving process.